Analisis Laporan Keuangan Pt Waskita Karya, Pt Adhi Karya, Danhutama Karya Periode 2022 – 2024 oleh Kelompok 2 - Nia Anisyah; Veronica Erva Yorinda; Febrika Nurfianti; Cholis Hidayati (CV. ITTC INDONESIA, 2025)
This study aims to analyze the financial performance of three state-owned enterprises (SOEs) in the construction sector, namely PT Waskita Karya, PT Adhi Karya, and PT Hutama Karya, during the period 2022–2024. The methods employed include time series analysis to observe performance trends over time and cross-sectional analysis to compare financial performance among companies. The indicators used consist of liquidity, solvency, activity, and profitability ratios. The results indicate that PT Waskita Karya experienced a significant decline in financial performance, reflected in weakened liquidity and solvency conditions as well as negative profitability. PT Adhi Karya demonstrated relatively stable performance with adequate liquidity and positive profitability, although asset utilization efficiency tended to decline. Meanwhile, PT Hutama Karya showed a strong position in terms of liquidity and capital structure; however, its asset activity and profitability remained limited. Overall, the findings reveal distinct financial performance characteristics among the three construction SOEs.